THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND EMPLOYEE ENGAGEMENT ON THRIVING AT WORK: THE MEDIATING ROLE OF INNOVATIVE WORK BEHAVIOR - Vivy Nurmalitasari; Asri Laksmi Riani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze and test the factors that influence Leadership and Employee Engagement on Thriving at Work with Innovative Work Behavior as a Mediator. This study is a type of quantitative research with a causal relationship. This study uses a questionnaire distribution to obtain data. The unit of analysis of this study is employees of KERATON Regional Hospital, Pekalongan Regency. In this study, the independent variables are leadership style (X_1) and employee engagement (X_2). The dependent variable in this study is thriving at work (Y). The mediating variable affects the relationship between the independent and dependent variables. This study uses innovative work behavior (M). The population in this study were 689 employees at KERATON Regional Hospital and a total sample of 225. Data analysis in this study was carried out using structural equation modeling (SEM) through Smart PLS (Partial Least Squares) software. Leadership Style has a positive effect on Thriving at Work, so the first hypothesis is accepted. Employee Engagement has a positive effect on Thriving at Work, so the second hypothesis is accepted. Leadership Style has a positive effect on Thriving at Work with Innovative Work Behavior as a mediating variable, so the third hypothesis is accepted. Employee Engagement has a positive effect on Thriving at Work with Innovative Work Behavior as a mediating variable, so the fourth hypothesis is accepted. Keywords: Leadership, Employee Engagement, Thriving at Work, Innovative Work Behavior